An empirical study to demonstrate that EdDSA can be used as a performance improvement alternative to ECDSA in Blockchain and IoT - J, Guruprakash; Koppu, Srinivas (Informatica, 2022)
Digital signatures are a vital part of the digital world. The trust factor in the digital world is ensured with a digital signature. Over the evolution, the purpose remained constant, but the applicability and frontier continued to evolve, thus raising the demand for continuous performance, security level and computational improvement. Especially with emerging IoT, blockchain and cryptocurrency, the digital signature security level and performance improvement demand continue to rise. A digital signature scheme (DSS) is used to generate signatures. This paper investigates the widely used elliptic curve digital signature algorithm (ECDSA) and its application to blockchain and IoT. Then, we performed an empirical comparison of ECDSA with the Edwards curve digital signature algorithm (EdDSA). The study concludes by showing that EdDSA is superior to ECDSA and can be applied in blockchain and IoT domains to reap immediate benefits. Digitalni podpisi so pomemben del digitalnega sveta. Faktor zaupanja v digitalnem svetu je zagotovljen z digitalnim podpisom. Z razvojem je namen ostal nespremenjen, vendar sta se uporabnost in meja še naprej razvijala, kar je povečalo povpraševanje po nenehni zmogljivosti, ravni varnosti in izboljšanju računalništva. Zlasti z nastajajočimi IoT, blockchain in kriptovalutami se povpraševanje po stopnji varnosti digitalnega podpisa in izboljšanju zmogljivosti še naprej povečuje. Za ustvarjanje podpisov se uporablja shema digitalnega podpisa (DSS). Ta članek raziskuje široko uporabljen algoritem za digitalno podpisovanje eliptične krivulje (ECDSA) in njegovo uporabo za blockchain in internet stvari. Nato smo izvedli empirično primerjavo ECDSA z algoritmom digitalnega podpisa Edwardsove krivulje (EdDSA). Študija se zaključi tako, da pokaže, da je EdDSA boljša od ECDSA in se lahko uporablja v domenah blockchain in IoT za takojšnje koristi.